Do political institutions matter for economic performance? A political economy analysis for Latin American countries - Jerabek, Marketa Maria (2016)
It seems appropriate to compare countries with a similar historical background and a different but comparable level of economic performance in order to make conditional statements. Studies about political institutions and economic performance in Latin American countries were conducted principally in qualitative analyses. The main objective of this study was an attempt based on the political economy to answer the question if different political institutions can explain economic performance in a time series cross section regression analysis. Using 18 Latin American countries for the years 1975-2010 the result of this research permits the conclusion, that political institutions such as political regime, electoral system, federalism on municipal level, partly the ideological polarization degree of executive´s party and the parties in legislature and the stability of a political regime matter for economic performance. Nevertheless, leaping to conclusions about clear causality would be careless and precipitous as the problem of endogeneity of political institutions has not been properly resolved in this research.